Pharmacokinetics and safety of repirinast tablets in healthy Chinese subjects (Brazilian Journal of Pharmaceutical Sciences, 2018)
Repirinast is a new, synthetic, disodium cromoglycate-like antiallergic agent for oral administration in humans. This study evaluated the safety, tolerability and pharmacokinetics of repirinast tablets in healthy Chinese volunteers. This was a phase I, open-label, randomized, single- and multiple-dose study. Subjects were assigned to receive a single dose of repirinast tablet at either 150, 300, or 450 mg, or multiple doses of 150 mg twice daily for 5 days. Plasma samples were analyzed with LC-MS/MS. Pharmacokinetic parameters of active metabolite MY-1250 (deesterified repirinast) were calculated using non-compartmental analysis with WinNonlin software. Statistical analysis was performed using SPSS software. All adverse events (AEs) were mild and of limited duration. No serious adverse event (SAE), death or withdrawal from the study was observed. In the single-dose study, Cmax was reached at about 0.75 hour, and the mean t1/2 was approximately 16.21 hours. Area under curve (AUC) and Cmax increased with dose escalation, but dose proportionality was not observed over the range of 150 to 450 mg. In the multiple-dose study, the steady-state was reached within 3 days with no accumulation. Repirinast tablet was well tolerated in healthy Chinese subjects.